Purification and functionalization of carbon nanotubes by classical and advanced oxidation processes - Escobar, Mariano Martin (2009)
Advanced oxidation technologies (AOT) were applied for the production of accurately controlled oxidized multi-walled carbon nanotubes. Fenton process is effective to get carboxylic (-COO - or -COOH) and OH groups on the surface of carbon nanotubes while Photofenton and UV/H 2O 2 processes mostly produce OH groups on surface of multiwalled carbon nanotubes (MWCNT). All of them preserve the structure of MWCNT allowing to achieve accurately controlled oxidized MWCNT. Fourier transform infrared spectroscopy (FTIR) and thermogravimetical analysis (TGA) show that the acid treatment is the more efficient technique to generate COOH groups on MWCNT surface. However, this chemical technique generates strong damages on the MWCNT structure, as demonstrated by TGA, field emission scanning electron microscopy and transmission electron microscopy results. Copyright © 2009 American Scientific Publishers.